Re-Visioning Public Health Approaches for Protecting Children - Lonne, Bob; Scott, Deb; Higgins, Daryl; Herrenkohl, Todd I. (Child Maltreatment, Contemporary Issues in Research and Policy, 2019)
This volume provides readers around the globe with a focused and comprehensive examination of how to prevent and respond to child maltreatment using evidence-informed public health approaches and programs that meet the needs of vulnerable children, and struggling families and communities. It outlines the system failures of contemporary forensically-driven child protection practice. Detailed guidance is provided about how to re-think earlier intervention strategies, and establish stronger and more effective programs and services that prevent maltreatment at the population level. Service user and stakeholder perspectives, particularly from marginalized groups including Indigenous peoples, highlight how public health approaches can better support families and keep children safe. Case studies from different countries grapple with the fraught nature of large system change and the various strategies needed to effect multi-level reforms. Presenting the reader with an array of innovative services used in different institutional and community context, this volume confronts the complex challenges found in implementing successful prevention programs that are aligned with diverse cultural and political environments and community expectations.